2011
DOI: 10.1002/cjoc.201190239
|View full text |Cite
|
Sign up to set email alerts
|

A New and Efficient Procedure for Synthesis of 1,5-Benzodiazepine Derivatives in Solution and under Solvent-Free Conditions

Abstract: Borax/phosphorous oxychloride (BPO) efficiently catalyzes the preparation of 1,5-benzodiazepine derivatives of o-phenylenediamines and ketones in solvent-free and solution conditions. The reaction proceeds efficiently under ambient conditions giving excellent yields of the products. This new protocol allows the recycling of catalyst with no loss in its potency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In the past decade, the biological interest of 1,5-benzodiazepines have been extended to curing several diseases such as cancer, viral infections, and cardiovascular disorders. , Depending on the substitution pattern and nature of substituents, benzodiazepines can have a wide range of half-lives. Moreover, 1,5-benzodiazepines are key synthons for the synthesis of various fused ring systems such as triazolo-, oxadiazolo-, oxazino-, or furano-benzodiazepines. Over the past several years, considerable studies have been reported for the synthesis of 1,5-benzodiazepines utilizing ytterbium triflate, gallium­(III)­triflate, erbium­(III)­triflate, scandium­(III)­triflate, ytterbium perfluorooctanesulfonate, BF 3 -etherate, p -toulenesulfonic acid, NaBH 4 , MgO/POCl 3 , polyphosphoric acid, CeCl 3 -NaI/SiO 2 , Al 2 O 3 /P 2 O 5 , sulfated zirconia, 1,3- n -dibutylimidazolium bromide, SbCl 3 -Al 2 O 3 , iodine, magnesium perchlorate, sodium dodecyl sulfate, Ag 3 PW 12 O 40 , zinc chloride, dodecyl sulfonic acid, piperidine acetic acid, La­(NO 3 ) 3 , SmI 2 , sulfamic acid, organic acid, HClO 4 -silica, YbCl 3 , ceric ammonium nitrate, N -bromosuccinimide, acetic acid/MW, (NH 4 )­H 2 PW 12 O 40 , SnCl 2 , K10-montmorillonite, Zn-montmorillonite heterogeneous catalysts borax/phosphorus oxychloride, amberlyst-15, InBr 3 , InCl 3 , NbCl 5 , and RuCl 3 · x H 2 O as catalysts. In addition, a solvent-free procedure has been reported for the synthesis of 1,5-benzodiazepines using iodine, silver nitrate, and HBF 4 -SiO 2 as catalysts at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, the biological interest of 1,5-benzodiazepines have been extended to curing several diseases such as cancer, viral infections, and cardiovascular disorders. , Depending on the substitution pattern and nature of substituents, benzodiazepines can have a wide range of half-lives. Moreover, 1,5-benzodiazepines are key synthons for the synthesis of various fused ring systems such as triazolo-, oxadiazolo-, oxazino-, or furano-benzodiazepines. Over the past several years, considerable studies have been reported for the synthesis of 1,5-benzodiazepines utilizing ytterbium triflate, gallium­(III)­triflate, erbium­(III)­triflate, scandium­(III)­triflate, ytterbium perfluorooctanesulfonate, BF 3 -etherate, p -toulenesulfonic acid, NaBH 4 , MgO/POCl 3 , polyphosphoric acid, CeCl 3 -NaI/SiO 2 , Al 2 O 3 /P 2 O 5 , sulfated zirconia, 1,3- n -dibutylimidazolium bromide, SbCl 3 -Al 2 O 3 , iodine, magnesium perchlorate, sodium dodecyl sulfate, Ag 3 PW 12 O 40 , zinc chloride, dodecyl sulfonic acid, piperidine acetic acid, La­(NO 3 ) 3 , SmI 2 , sulfamic acid, organic acid, HClO 4 -silica, YbCl 3 , ceric ammonium nitrate, N -bromosuccinimide, acetic acid/MW, (NH 4 )­H 2 PW 12 O 40 , SnCl 2 , K10-montmorillonite, Zn-montmorillonite heterogeneous catalysts borax/phosphorus oxychloride, amberlyst-15, InBr 3 , InCl 3 , NbCl 5 , and RuCl 3 · x H 2 O as catalysts. In addition, a solvent-free procedure has been reported for the synthesis of 1,5-benzodiazepines using iodine, silver nitrate, and HBF 4 -SiO 2 as catalysts at room temperature.…”
Section: Introductionmentioning
confidence: 99%